(Invited) Probing the Influence of the Dielectric Environment on Charge Carrier Dynamics in Semiconducting Polymers - Ferguson, Andrew J; Gish, Melissa; Kopcha, William; Mohapatra, Aiswarya Abhisek; Carr, Joshua; Rumbles, Garry; Reid, Obadiah; Greenaway, Ann L (Meeting abstracts (Electrochemical Society), 2024)
Pi-conjugated semiconducting polymers have garnered attention for a variety of electronic and optoelectronic applications, such as field-effect transistors, thermoelectric generators, and photovoltaic devices. In these systems, the charge carrier dynamics are primarily governed by the properties of the polaron and the polymer microstructure. More recently, there has been growing interest in the suitability of these polymer for electrochemical transistors and (photo)electrochemical applications, where the understanding is further complicated by the presence of ions and solvent molecules, as well as the dynamic transport of these species into the semiconducting polymer. Here, we will employ steady-state and transient spectroscopic techniques to probe the influence of charge carrier doping, as well as the extrinsic and local dielectric environments, on charge carrier generation, transport, and recombination in prototypical semiconducting polymer(s). Incorporation of electrochemical techniques enables in-situ spectroscopic measurements that mimic operando conditions. Our observations will provide a better understanding of the factors that control the carrier dynamics in these compositionally complex systems and will have implications for their viability and optimization for (photo)electrochemical applications.